Regioselective and Stereospecific Deuteration of Bioactive Aza Compounds by the Use of Ruthenium Nanoparticles1. (19th November 2013) - Pieters, Grégory; Taglang, Céline; Bonnefille, Eric; Gutmann, Torsten; Puente, Céline; Berthet, Jean‐Claude; Dugave, Christophe; Chaudret, Bruno; Rousseau, Bernard
Abstract An efficient H/D exchange method allowing the deuteration of pyridines, quinolines, indoles, and alkyl amines with D2 in the presence of Ru@PVP nanoparticles is described. By a general and simple procedure involving mild reaction conditions and simple filtration to recover the labeled product, the isotopic labeling of 22 compounds proceeded in good yield with high chemo‐ and regioselectivity. The viability of this procedure was demonstrated by the labeling of eight biologically active compounds. Remarkably, enantiomeric purity was conserved in the labeled compounds, even though labeling took place in the vicinity of the stereogenic center. The level of isotopic enrichment observed is suitable for metabolomic studies in most cases. This approach is also perfectly adapted to tritium labeling because it uses a gas as an isotopic source. Besides these applications to molecules of biological interest, this study reveals a rich and underestimated chemistry on the surface of ruthenium nanoparticles.